Relations of Social Media Addiction with Impulsivity, Narcissism and Assertiveness in Belarusian and Ukrainian University Students - Viktor P. Sheinov; Anton S. Dziavitsyn (Peoples' Friendship University of Russia (RUDN University), 2022)
Social media addiction (SMA) is one of the most widespread non-medical addictions. Previous research has found positive associations between SMA and depression, anxiety, stress, and other symptoms and signs of mental ill-being. The purpose of this study is to identify and compare the associations with specific manifestations of psychological distress (e.g., impulsivity, narcissism, vulnerability to manipulation, low assertiveness, smartphone addiction and its factors) in groups of Belarusian and Ukrainian university students. The study was conducted using the following diagnostic tools: SMA-15 Questionnaire by V.P. Sheinov A.S. Dziavitsyn; a short version of the SAS-16 questionnaire Smartphone Addiction Scale by V.P. Sheinov; Assessment of the Degree of Vulnerability of an Individual from Manipulative Influences by V.P. Sheinov; Questionnaire for Diagnosing the Potential of Communicative Impulsivity by V.A. Losenkov; and Narcissistic Questionnaire by E. Kot. The sample consisted of 604 university students, including 403 residents of Belarus (77% females) and 201 residents of Ukraine (53% females). The mean age of the participants was 21.5 years (SD = 5.17). The results of the study revealed: (1) positive associations of SMA with impulsivity, smartphone addiction and its factors ('loss of control,' 'fear of rejection' and user's 'euphoria'), common for the Belarusian and Ukrainian students; (2) positive associations of SMA with narcissism for the Belarusian male and female students as well as for the Ukrainian male students; and (3) a negative association of SMA with assertiveness for the Ukrainian male and female students and for the Belarusian female students (for the latter, a negative association with vulnerability to manipulation was also found). In practical terms, the revealed associations between SMA and a number of symptoms and signs of psychological distress provide material for explanatory work with students about the dangers of excessive involvement in social media.